Haemaphysalis calva Nuttall and Warburton 1915 ... - Petney, Trevor N.; Boulanger, Nathalie; Saijuntha, Weerachai; Chitimia-Dobler, Lidia; Pfeffer, Martin; Eamudomkarn, Chatanun; Andrews, Ross H.; Ahamad, Mariana; Putthasorn, Noppadon; Muders, Senta V.; Petney, David A.; Robbins, Richard G. (Zenodo, 2019)
Haemaphysalis calva Nuttall and Warburton, 1915 This is a rare Oriental species that has been recorded from peninsular Malaysia and Thailand, as well as Indonesia (Hoogstraal and Wassef 1981; Tanskul et al. 1983). It is a parasite predominantly of sambar deer, but has also been recorded from wild pig, palm civet, Himalayan brown bear (Ursus arctos isabellinus) and water buffalo (Hoogstraal and Wassef 1981). Adults and nymphs are described in Hoogstraal and Wassef (1981). ... : Published as part of Petney, Trevor N., Boulanger, Nathalie, Saijuntha, Weerachai, Chitimia-Dobler, Lidia, Pfeffer, Martin, Eamudomkarn, Chatanun, Andrews, Ross H., Ahamad, Mariana, Putthasorn, Noppadon, Muders, Senta V., Petney, David A. & Robbins, Richard G., 2019, Ticks (Argasidae, Ixodidae) and tick-borne diseases of continental Southeast Asia, pp. 1-89 in Zootaxa 4558 (1) on page 23, DOI: 10.11646/zootaxa.4558.1.1, http://zenodo.org/record/2613120 ...